Les « Monuments français inédits » (1806-1839) de N.-X. Willemin et la découverte des « Antiquités nationales » - Arquié-Bruley, Françoise (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1983)
Reference works which marked their day and were improvements over what previously existed are normally taken for granted, eventually forgotten. The in part posthumous work of N.X. Willemin in selecting and publishing the ‘National Antiquities’ of France, is one of the earlier and more important histories of the arts on a comparative method, treating works front the sixth to seventeenth centuries as documents of the historical evolution of society. The art works discussed were not only in the leading Parisian and provincial museums and libraries, but from outstanding private collections as well, so the Monuments français inédits is the result of a complex series of relations between scholars, editors, collectors and dealers in the transitional period between Revolution and Restoration. Their identification and the characterization of their activities will provide scholars with a more secure foundation for further research in the early Romantic period which is as yet poorly documented.